PENGARUH ASSET SIZE, CLOSING PRICE, LIKUIDITAS, VARIAN RETURN, DAN VOLUME PERDAGANGAN SAHAM TERHADAP BID-ASK SPREAD PADA PERUSAHAAN REAL ESTATE DAN PROPERTI YANG TERDAFTAR DI BEI - Leoni Bidara Rasyidi; Yunika Murdayanti (Jurnal Ilmiah Wahana Akuntansi, 2013)
In investing there money, the investors always need information. One of them is stock bid ask spread. But they usually don’t notice it. In fact, stock bid ask spread can reflect trading volume, asset size, stock rise level, etc. The purpose of this research was to analyze the influences of asset size, closing price, liquidity, return varian, and trading volume to stock bid ask spread in Indonesian Stock Exchange either individually or simultaneously. This research used double regression analysis with bid ask spread as a dependent variable and asset size, closing price, liquidity, return varian, and trading volume as independent variables. The period that was used was 2006 until 2009 with 32 emitents as the samples. These samples were collected by purposive sampling method. The results of this research showed that there were significant influences of asset size, closing price, liquidity, return varian, and trading volume to bid ask spread simultaneously. There were also significant influences of asset size and closing price to bid ask spread individually. Keywords : bid ask spread, asset size, closing price, liquidity, return varian , and trading volume.